2020
DOI: 10.1093/clinchem/hvaa296
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-Rich Lipoprotein Remnants and Cardiovascular Disease

Abstract: Background Triglycerides, cholesterol, and their metabolism are linked due to shared packaging and transport within circulating lipoprotein particles. While a case for a causal role of cholesterol-carrying low-density lipoproteins (LDLs) in atherosclerosis is well made, the body of scientific evidence for a causal role of triglyceride-rich lipoproteins (TRLs) is rapidly growing, with multiple lines of evidence (old and new) providing robust support. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 100 publications
0
60
0
Order By: Relevance
“…Dyslipidemia is a major pathogenic risk factor for atherosclerosis, and numerous studies 6 , 9–12 , 17 have confirmed that dyslipidemia is not only an independent risk factor for CHD but also closely related to ISR. For the postoperative lipid management of PCI patients, lipid-lowering therapy is recommended for the secondary prevention of PCI patients according to the guidelines for PCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dyslipidemia is a major pathogenic risk factor for atherosclerosis, and numerous studies 6 , 9–12 , 17 have confirmed that dyslipidemia is not only an independent risk factor for CHD but also closely related to ISR. For the postoperative lipid management of PCI patients, lipid-lowering therapy is recommended for the secondary prevention of PCI patients according to the guidelines for PCI.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have shown that dyslipidemia and ISR are indissolubly linked. 6 To the best of our knowledge, the majority of the previous related literature 7 , 8 has concentrated on investigating the impact of low-density lipoprotein cholesterol (LDL-C) levels on ISR. However, a growing number of studies have demonstrated that patients are still at considerable risk of developing cardiovascular disease even after lowering LDL-C to recommended concentrations and controlling other risk factors (eg, hypertension and diabetes).…”
Section: Introductionmentioning
confidence: 99%
“…We found that HDL subsets were increased in young trans-women treated with estradiol (on puberty blockers) and were lost in young trans-men treated with testosterone (on puberty blockers) where an increase in VLDL and LDL was detected. It is well reported that TG-rich VLDL particles are responsible for residual cardiovascular risk ( Duran and Pradhan, 2021 ). Of interest, no difference in VLDL or LDL subsets were seen in young trans-women, suggesting HDL levels and cellular lipid efflux to HDL may be more sensitive to estradiol fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…The chylomicron end products are known as remnants; the intermediate-density lipoproteins (IDL) are the corresponding ones for VLDLs. Some (remnants, IDLs, and the denser VLDLs) but not all TRLs are involved in the development of atherosclerotic cardiovascular disease [1][2][3] . As a result, clinicians should be able to discern in which cases TRLs should be considered as treatment targets (besides low-density lipoprotein [LDL]-cholesterol).…”
Section: Rev Invest Clin (Ahead Of Print) In-depth Reviewmentioning
confidence: 99%